The relationship between parenting styles, psychological flexibility, and self-esteem on mental health among Malaysian young adults - Ismail, Isnafatihah; Ma’rof, Aini Azeqa; Rosnon, Mohd Roslan (Human Resources Management Academic Research Society (HRMARS), 2024)
This study examines the role of parenting techniques and psychological qualities on prosocial behavior. It analyzes data from 428 participants to assess the impact of environmental and personal factors on these behaviors. The main emphasis is placed on three distinct parenting styles, namely authoritative, authoritarian, and permissive, as well as individual psychological attributes like as self-esteem and psychological flexibility. The research employs multiple regression analysis to measure the impact of these variables on prosocial behavior, explaining 61.5% of the variability. The findings indicate that authoritative parenting has a favorable impact on prosocial behavior, indicating that a caring yet organized approach encourages the development of prosocial tendencies. Authoritarian and permissive parenting styles, in contrast, have a negative correlation with prosocial conduct. This suggests that excessively severe or tolerant approaches may hinder the development of socially advantageous behaviors. Psychological characteristics also have a substantial impact. Self-esteem is identified as the most influential factor, highlighting the significance of an individual's belief in their social talents. Psychological flexibility has a beneficial effect, indicating that being adaptable in social contexts improves prosocial conduct. These findings emphasize the crucial importance of psychological well-being and flexibility in encouraging behaviors that are advantageous to others. This study enhances our comprehension of the elements that promote prosocial conduct, highlighting the necessity for educational and community initiatives that improve psychological characteristics and promote successful parenting methods. By gaining a deeper comprehension of the factors that influence prosocial conduct, policymakers and educators can create tactics to improve cooperative and supportive relationships within communities, thus enhancing the social structure of our surroundings.